2023
DOI: 10.1039/d3ra00223c
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized graphene oxide-based lamellar membranes for organic solvent nanofiltration applications

Abstract: In this study, two-dimensional graphene oxide-based novel membranes were fabricated by modifying the surface of graphene oxide nanosheets with six-armed poly(ethylene glycol) (PEG) at room conditions and used for organic solvent nanofiltration applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…However, developing robust, high-performance materials and dealing with humidity in hostile environments are exceedingly difficult for novel membrane technology applications. In this regard, a large range of materials have been studied, including polymers, zeolite, metal-organci frameworks (MOFs), covalent organic frameworks (COFs), graphene, and metal carbides and nitrides (Mxene) [29][30][31][32][33][34][35][36][37][38][39][40][41], but their market potential is constrained by their low selectivity and unstable nature. So, the scientific community continues to place a high focus on choosing materials with advanced selectivity, stability, and flux.…”
Section: Gas Separationmentioning
confidence: 99%
“…However, developing robust, high-performance materials and dealing with humidity in hostile environments are exceedingly difficult for novel membrane technology applications. In this regard, a large range of materials have been studied, including polymers, zeolite, metal-organci frameworks (MOFs), covalent organic frameworks (COFs), graphene, and metal carbides and nitrides (Mxene) [29][30][31][32][33][34][35][36][37][38][39][40][41], but their market potential is constrained by their low selectivity and unstable nature. So, the scientific community continues to place a high focus on choosing materials with advanced selectivity, stability, and flux.…”
Section: Gas Separationmentioning
confidence: 99%
“…Molecular separations are processes that demand a lot of energy and can be employed in various separation industries. 125–128 The global shift towards sustainable production necessitates the development of novel, energy-efficient separation techniques. According to Livingston et al , 129 the filtration processes can be categorized based on (i) the propelling force required for the separation; (ii) the size of the rejected solute or, in turn, the size of the pore; and (iii) the transport mechanism governing the separation.…”
Section: Water Purification and Desalination Applicationsmentioning
confidence: 99%
“…Recent developments have focused on enhancing the efficiency and stability of these membranes. , For instance, a study demonstrated that the cross-linking of divalent cations could improve resistance against swelling in partially reduced GO membranes, leading to improved dye-rejection efficiencies of up to 98.88% for certain dyes . In another research by Chandio et al, a GO membrane was fabricated by employing a cross-linker, which was chosen to be serine amino acid (SAA), and reducing agent.…”
Section: Introductionmentioning
confidence: 99%